2020
DOI: 10.1212/wnl.0000000000010318
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal antibody prevalence in children with seizures under 3 years

Abstract: Objective:To report the prevalence of anti-neuronal antibodies in a prospectively whole nation cohort of children presenting with seizures before their third birthday.Methods:This was a prospective population-based national cohort study involving all children presenting with new onset epilepsy or complex febrile seizures before their 3rd birthday over a three-year period. Patients with previously identified structural, metabolic or infectious cause for seizures were excluded. Serum samples were obtained at fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Forest plot of the incidence or prevalence of seizures in AE patients (A); forest plot of the incidence or prevalence of AE in epilepsy patients (B); forest plot of the incidence or prevalence of antibody positivity in patients with epilepsy (C); forest plot of the incidence or prevalence of anti-NMDAR in epilepsy patients (D); forest plot of the incidence or prevalence of anti-LGI1 in epilepsy patients (E); forest plot of the incidence or prevalence of anti-CASPR2 in epilepsy patients (F). [46][47][48][49][50]54]. The pooled-period prevalence of anti-LGI1 in epilepsy in these studies was 1% (95% CI: 0.00-0.02, p = 0.040, Z = 3.20, I 2 = 54.4%) (Fig.…”
Section: Antibody Positivity In Epilepsymentioning
confidence: 80%
See 4 more Smart Citations
“…Forest plot of the incidence or prevalence of seizures in AE patients (A); forest plot of the incidence or prevalence of AE in epilepsy patients (B); forest plot of the incidence or prevalence of antibody positivity in patients with epilepsy (C); forest plot of the incidence or prevalence of anti-NMDAR in epilepsy patients (D); forest plot of the incidence or prevalence of anti-LGI1 in epilepsy patients (E); forest plot of the incidence or prevalence of anti-CASPR2 in epilepsy patients (F). [46][47][48][49][50]54]. The pooled-period prevalence of anti-LGI1 in epilepsy in these studies was 1% (95% CI: 0.00-0.02, p = 0.040, Z = 3.20, I 2 = 54.4%) (Fig.…”
Section: Antibody Positivity In Epilepsymentioning
confidence: 80%
“…Therefore, we calculated the incidence/prevalence of NMDAR, IGL1, and CAPSR2 in epilepsy, which are the common antibodies associated with AE. Eleven studies examined NMDAR antibodies [41,42,45,46,50,53,54,[56][57][58]60]. After excluding one study that focused only on anti-NMDAR encephalitis [53], we found that the pooled-period prevalence of anti-NMDAR in epilepsy was 1% (95% CI: 0.01-0.02, p < 0.0001, Z = 4.74, I 2 = 88.8%) (Fig.…”
Section: Antibody Positivity In Epilepsymentioning
confidence: 95%
See 3 more Smart Citations